The role of the otolaryngologist in the evaluation and diagnosis of eosinophilic esophagitis. (30th November 2016) - Kubik, Mark; Thottam, Prasad; Shaffer, Amber; Choi, Sukgi
Abstract : Objective: To describe the clinical presentation and role of the otolaryngologist in the evaluation of eosinophilic esophagitis (EoE) at a tertiary pediatric hospital. Study Design: Retrospective review. Methods: Records from pediatric patients with a diagnosis of EoE from 2003 to 2015 were reviewed. Study variables were analyzed to compare patients presenting to different specialties. Results: Two hundred and fifty‐one patients with EoE were evaluated. The median age at diagnosis was 9.0 years (range 0.8–19.0); 73% were male. Sixty‐seven percent of patients initially presented to gastroenterology and 18% to otolaryngology. Time from initial presentation to diagnosis did not differ between the patients presenting to the two specialties (median 2.3 vs. 2.0 months, P = 0.510). Overall, 26% presented with airway symptoms (stridor, chronic cough, croup, or dysphonia). Patients diagnosed by the otolaryngology service were younger (3.4 vs. 10.4 years, P < 0.0001), had a higher incidence of airway symptoms (68% vs. 15%, P < 0.001), and demonstrated fewer gastrointestinal symptoms (86% vs. 100%, P < 0.001). Conclusion: Patients with EoE frequently present to otolaryngology undiagnosed in the first 5 years of life, making esophagoscopy with biopsy an important adjunct to airway endoscopy in children with refractory aerodigestive symptoms. Otolaryngologists are uniquely poised to facilitate early diagnosis and initiation of therapy for these children, potentially reducing long‐term sequelae. Level of Evidence: 4. Laryngoscope, 127:1459–1464, 2017